Healthcare costs and loss of productivity in patients with trapeziometacarpal osteoarthritis. (November 2015) - Marks, M.; Vliet Vlieland, T. P. M.; Audigé, L.; Herren, D. B.; Nelissen, R. G. H. H.; van den Hout, W. B.
The objective of this study was to analyse healthcare and productivity costs in patients with trapeziometacarpal osteoarthritis. We included 161 patients who received surgery or steroid injection and calculated their healthcare costs in Euro (€) over 1 year. Patients filled out the Work Productivity and Activity Impairment Questionnaire to assess loss of productivity at baseline, and after 3, and 12 months. In the surgical group, loss of productivity among employed patients first increased and then decreased (50%, 64%, and 25% at 0, 3, and 12 months). Productivity was more stable over time in the injection group (52%, 38%, and 48%). In the surgical group, estimated total annual healthcare and productivity costs were €5770 and €5548, respectively. In the injection group, healthcare and productivity costs were €348 and €3503. These findings highlight the need for assessing productivity costs to get a comprehensive view of the costs associated with a treatment. Level of Evidence III